Analisis Perbandingan Rasio Keuangan Untuk Menilai Kinerja Keuangan Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2023 - Allesia Putri Wijaya Sutikno; Riska Septi Ariani; Fernianda Wahyu Ramadanthy; Siti Ambar Mukti Puji Lestari; Amelia Vega Buana; Cholis Hidayati (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the comparison of financial ratios (liquidity, activity, solvency, profitability, and market) in five food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2018–2023 period using a descriptive quantitative method and secondary data. The results reveal performance variations, where PT Campina Ice Cream Industry Tbk excels in liquidity, PT Indofood CBP Sukses Makmur Tbk in activity and market ratios, PT Siantar Top Tbk in profitability, and PT Mayora Indah Tbk in solvency. Each company has its strengths and weaknesses, highlighting the importance of financial ratio evaluation to enhance competitiveness and attract investments.